Usage count of hydrogen-based hybrid energy storage systems: An analytical review, challenges and future research potentials - Wali S.B.; Hannan M.A.; Abd Rahman M.S.; Alghamdi H.A.; Mansor M.; Ker P.J.; Tiong S.K.; Mahlia T.M.I. (Elsevier Ltd, 2024)
Electricity generation and consumption must undergo a substantial transformation as part of the global energy transition towards decarbonization. Hydrogen-based hybrid energy storage systems (HESS) have the potential to replace the existing fossil fuel-based energy generation due to their high energy density and long storage capacity. This study has introduced a novel indicator usage count instead of citation analysis to obtain the top 100 articles in the field of hydrogen-based HESS because of the factors such as reduction of time lag, recentness and domain independency. After the filtration process, the top 100 articles with the highest usage count are obtained by providing an extensive search in the Scopus database from the year 20122021. An extensive comparative study between usage count and citation analysis among the selected top 100 articles is provided. Moreover, a detailed keyword co-occurrence network (KCN) analysis along with comprehensive reviews concerning HESS modelling, optimization objectives, algorithms, system constraints, and research gaps are presented. The review emphasizes the benefits and drawbacks of hydrogen-based HESS and analyzes the obstacles associated with their application, such as the system's high cost, technical complexity, socio-economic and environmental impact and safety concerns, which can provide the researchers with a clearer picture for future research and development. Finally, the article conveys some suggestions and directions, which can act as a roadmap toward achieving reliable and sustainable next-generation hydrogen-based HESS. 2023 Hydrogen Energy Publications LLC